Answer:
a = p + 8 - b
Explanation:
Step 1: Add 8 both sides
![\displaystyle{a+b-8+8=p+8}\\\\\displaystyle{a+b=p+8}](https://img.qammunity.org/2023/formulas/mathematics/high-school/bgby4gg20woasa932cwaegy9gapn6vpljz.png)
Step 2: Subtract b both sides
![\displaystyle{a+b-b=p+8-b}\\\\\displaystyle{a=p+8-b}](https://img.qammunity.org/2023/formulas/mathematics/high-school/cw80d14jtk2i4a6lcpcnbt2i0329wqg63v.png)
Note: You can also subtract b both sides first then add 8 both sides.
Therefore, the new equation when a-term is the subject is
.
Please let me know if you have any questions!